2022
DOI: 10.12800/ccd.v17i53.1925
|View full text |Cite
|
Sign up to set email alerts
|

Methods for estimating biological maturation indeveloping and growing athletes: A literature review

Abstract: Métodos de estimación de la maduración biológica en deportistas en etapa de desarrollo y crecimiento: Revisión bibliográfica Albaladejo-Saura et al. 66 Métodos de estimación de la maduración biológica en deportistas en etapa de desarrollo y crecimiento: Revisión bibliográfica

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…The senior category had the highest number of reported physical complaints. This is consistent with Albaladejo-Saura et al, (2022) and AAOS (2013) data that adolescents are more susceptible to sports injuries because they participate in sports earlier and more intensively and are in the process of rapid growth and neurobiological maturation while navigating an increasingly competitive and selective psychosocial environment.…”
Section: Physical Complaintssupporting
confidence: 90%
“…The senior category had the highest number of reported physical complaints. This is consistent with Albaladejo-Saura et al, (2022) and AAOS (2013) data that adolescents are more susceptible to sports injuries because they participate in sports earlier and more intensively and are in the process of rapid growth and neurobiological maturation while navigating an increasingly competitive and selective psychosocial environment.…”
Section: Physical Complaintssupporting
confidence: 90%
“…However, to our knowledge, this is the first study to show that the effects on body composition after performing HIIT-based training depends on sex, in adolescents around the age at peak height velocity (APHV). Previous studies have shown that hormonal changes around APHV, related to the maturational process, have significant effects on body composition, with an increase in muscle mass and a decrease in fat mass found in males; and an increase in fat mass in females ( 38 , 39 ). Thus, this aspect could be modulating the effects of HIIT on body composition, so results of current research must be interpreted with some reservations due to maturation has not been controlled, among other polluting factors.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the limitations of the study, firstly, the gold standard to evaluate the biological maturation, which is wrist and hand radiography [11], was not used to determine the maturity status of the players. This method, although it is the reference method, also has certain disadvantages since it uses X-rays and exposes the participants to certain radiation; moreover, it is a time-consuming, invasive method with a high cost [65]. Another noninvasive option, easy to apply and widely used in previous research with athletes [13,26], is maturity estimation equations based on regression equations.…”
Section: Discussionmentioning
confidence: 99%
“…The one used in this study was the one described by Mirwald et al [34], as it has been one of the most widely used in the adolescent athlete population in different disciplines [13]. In addition, the considerations identified in the literature were followed to avoid the inclusion of errors in the estimation of the maturity offset [65]. The sample size and selection of the same were also a limitation, which limits the extrapolation of the results to populations that do not have similar characteristics, and the study design, which, being cross-sectional, was not possible to follow up on how biological maturation affects throughout adolescence.…”
Section: Discussionmentioning
confidence: 99%